To set up the equations based on the problem statement:
Let \( a \) be Tony's current age. Therefore, Andrea's current age is \( a - 6 \) since Andrea is 6 years younger than Tony.
In two years, Tony's age will be \( a + 2 \), and Andrea's age will be \( (a - 6) + 2 = a - 4 \).
According to the problem, in two years, Tony will be three times as old as Andrea, which gives us the equation:
\[ a + 2 = 3((a - 6) + 2) \]
This simplifies to:
\[ a + 2 = 3(a - 4) \]
Now let's look for the equation from the options provided. The only equation that matches our setup is:
a + 2 = 3(a − 6 + 2)
So the correct equation you can use to find Andrea's and Tony's current ages is:
a + 2 = 3(a - 6 + 2).